Liposomal dry powders as aerosols for pulmonary delivery of proteins - Lu, Dongmei (Springer-Verlag, 2005)
The purpose of this research was to develop liposomal dry powder aerosols for protein delivery. The delivery of stable protein formulations is essential for protein subunit vaccine delivery, which requires local delivery to macrophages in the lungs. β-Glucuronidase (GUS) was used as a model protein to evaluate dry powder liposomes as inhaled delivery vehicles. Dimyristoyl phosphatylcholine:cholesterol (7∶3) was selected as the liposome composition. The lyophilization of liposomes, micronization of the powders, aerosolization using a dry powder inhaler (DPI), and in vitro aerodynamic fine particle fraction upon collection in a twinstage liquid impinger were evaluated. After lyophilization and jet-milling, the total amount of GUS and its activity, representing encapsulation efficiency and stability, were evaluated. The GUS amount and activity were measured and compared with freshly-prepared liposomes in the presence of mannitol, 43% of initial GUS amount, 29% of GUS activity after lyophilization and 36% of GUS amount, 22% of activity after micronization were obtained. Emitted doses from dry powder inhaler were 53%, 58%, 66%, and 73% for liposome powder:mannitol carrier ratios of 1∶0, 1∶4, 1∶9, and 1∶19. Fifteen percent of the liposome particles were less than 6.4 μm in aerodynamic diameter. The results demonstrate that milled liposome powders containing protein molecules can be aerosolized effectively at a fixed flow rate. Influences of different cryoprotectants on lyophilization of protein liposome formulations are reported. The feasibility of using liposomal dry powder aerosols for protein delivery has been demonstrated but further optimization is required in the context of specific therapeutic proteins.